Enhancing Student Engagement in Arabic Language Learning through iSpring Suite 11 - Alwi Nizar Al-Ghifari; Uswatun Hasanah; Hanan Mohammed Ali Zaid Al Nahari; Rose Mary Adelia Subagyo (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
The advancement of technology has significantly facilitated human activities, including in the educational sector. This study aimed to evaluate the effectiveness of the iSpring Suite 11 interactive learning media in enhancing students' interest and engagement in Arabic language learning at MAN 5 Garut. Employing a quasi-experimental design with pre-test and post-test control groups and a quantitative approach, data were collected through observation, interviews, questionnaires, tests, and documentation. The findings revealed that students' interest and activity levels were initially low, with mean scores of 32 and 50, respectively. After the intervention using iSpring Suite 11, these scores increased to 87 (very high interest) and 90 (very high activity). Statistical analysis showed a significant improvement in the experimental group (interest gain = 0.8; activity gain = 0.8), surpassing the control group (interest gain = 0.7; activity gain = 0.6). The study concludes that iSpring Suite 11 is more effective than conventional methods in fostering student interest and engagement in Arabic language education. Future research should explore the long-term effects of such technologies across different educational contexts and subject areas.